Reversible cross-linked foam articles and methods

By using a crosslinking composition selected from the group consisting of ethylene-based polymers and polar ethylene-based polymers and forming at a reprocessing temperature, the dynamic crosslinking characteristics of BiTEMPS methacrylate are solved, and the reprocessability and long-life use of the existing crosslinked foam products are achieved.

CN119677807APending Publication Date: 2025-03-21DOW GLOBAL TECHNOLOGIES LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380052372.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-15
Filing Date
2023-07-14
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The recyclability and reusability of existing crosslinked foam products is limited and it is difficult to reprocess by heating or mechanical shearing.

Method used

A crosslinking composition consisting of a selected ethylene polymer, a polar ethylene polymer and a combination thereof is used, and formed at a reprocessing temperature, and a dynamic crosslinking agent BiTEMPS methacrylate is used to form a reprocessable polymer composition.

Benefits of technology

Reprocessability of foam products is achieved, allowing fracture and re-formation of cross-linking networks at reprocessing temperatures, thereby re-processing and forming, extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677807A_ABST
    Figure CN119677807A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a foam article. In one embodiment, the foam article includes a crosslinked foam composition formed from a starting material comprising (i) a polymer selected from the group consisting of ethylene-based polymers, polar ethylene-based polymers, and combinations thereof, and (ii) a 2, 2, 6, 6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS) methacrylate. This results in a foam article consisting of a cross-linking composition comprising (i) a polymer selected from the group consisting of ethylene-based polymers, polar ethylene-based polymers, and combinations thereof, and (ii) a bond # imgabs0 # having the following structure (2).
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Polyolefin elastomer foams are widely used in consumer applications, such as footwear midsoles. Crosslinking can increase the viscosity of the polymer backbone, which is advantageous during the foaming process and provides enhanced mechanical properties to the resulting foam. Conventional crosslinking is usually induced by free radical methods (peroxides) or radiation to form C-C bonds. Conventional crosslinked foams are very stable and cannot be further dissociated by heating or mechanical shearing. Therefore, the recyclability and / or reusability of conventional crosslinked foam products is very limited or non-existent.

[0002] In light of global concerns regarding carbon neutrality and recyclability of plastic materials, the art recognizes the need for cross-linked foam articles that can be reprocessed and / or recycled. Summary of the invention

[0003] The present disclosure relates to a foam article. In one embodiment, the foam article includes a cross-linked foam composition formed from a starting material, the starting material comprising (i) a polymer selected from the group consisting of ethylene polymers, polar ethylene polymers, and combinations thereof, and (ii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS) methacrylate. This produces a foam article composed of a cross-linked composition, the cross-linked composition comprising (i) a polymer selected from the group consisting of ethylene polymers, polar ethylene polymers, and combinations thereof, and (ii) a bond having the following structure (2):

[0004]

[0005] Structure (2).

[0006] The present disclosure provides a method. In one embodiment, the method includes heating a foam article to a reprocessing temperature, the foam article being composed of a cross-linked composition comprising: (i) a polymer selected from the group consisting of an ethylene polymer, a polar ethylene polymer, and combinations thereof; and

[0007] (ii) A bond having structure (2)

[0008]

[0009] The foam article is formed from a starting material comprising (i) a polymer selected from the group consisting of ethylene polymers, polar ethylene polymers, and combinations thereof, and (ii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS) methacrylate. The method includes forming the foam article into a reprocessable polymer composition at a reprocessing temperature. The method includes forming the reprocessable polymer composition into a reprocessable preform at a reprocessing temperature. The method includes cooling the reprocessed preform to below the reprocessing temperature and forming a second article consisting of a recrosslinked polymer composition, the recrosslinked polymer composition consisting of (i) a polymer selected from the group consisting of ethylene polymers, polar ethylene polymers, and combinations thereof, and (ii) bonds having structure (2).

[0010] definition

[0011] All references to the Periodic Table of the Elements herein shall refer to the Periodic Table of the Elements published and copyrighted by CRC Press, Inc. in 2003. Furthermore, any reference to one or more groups shall be to the one or more groups reflected in such Periodic Table of the Elements using the IUPAC system for numbering groups. Unless stated to the contrary, implied by the context, or customary in the art, all parts and percentages are by weight. For purposes of U.S. patent practice, any patent, patent application, or publication referred to herein is incorporated herein by reference in its entirety (or its equivalent U.S. version is so incorporated by reference).

[0012] The numerical range disclosed herein includes all values ​​from the lower limit to the upper limit and including the lower limit and the upper limit. For a range containing clear values ​​(e.g., a range of 1 or 2, or 3 to 5, or 6, or 7), any sub-range between any two clear values ​​is included (e.g., the above range 1 to 7 includes 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).

[0013] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.

[0014] A "foaming agent" is a substance that is capable of creating a cellular structure in a composition through a foaming process.

[0015] The term "block copolymer" or "segmented copolymer" refers to a polymer comprising two or more chemically distinct regions or segments (referred to as "blocks") joined in a linear manner rather than in a pendant or grafted manner, i.e., a polymer comprising chemically distinct units joined end-to-end (covalently bonded) with respect to polymeric functionality. In one embodiment, the blocks differ in the amount or type of comonomer incorporated, density, amount of crystallinity, type of crystallinity (e.g., polyethylene versus polypropylene), crystallite size attributable to the polymer of such composition, type or degree of stereoisomerism (isotactic or syndiotactic), regioregularity or regioirregularity, amount of branching (including long chain branching or hyperbranching), uniformity, or any other chemical or physical property. Block copolymers are characterized by unique distributions of both polymer polydispersity (PDI or Mw / Mn) and block length distribution due to the effects of one or more shuttling agents in combination with one or more catalysts employed in their preparation.

[0016] The term "composition" as used herein refers to a mixture of materials which comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.

[0017] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequent listing any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of excludes any ingredient, step, or procedure not specifically recited or listed.

[0018] "Ethylene polymers" are polymers containing more than 50 mol% of polymerized ethylene monomers (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Ethylene polymers include ethylene homopolymers and ethylene copolymers (meaning units derived from ethylene and one or more comonomers). The terms "ethylene polymers" and "polyethylene" are used interchangeably. Non-limiting examples of ethylene polymers (polyethylene) include low density polyethylene (LDPE) and linear polyethylene. Non-limiting examples of linear polyethylene include linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), multi-component ethylene-based copolymers (EPE), ethylene / α-olefin multi-block copolymers (also known as olefin block copolymers (OBC)), substantially linear or linear plastomers / elastomers, and high density polyethylene (HDPE). Generally speaking, polyethylene can be produced in a gas phase fluidized bed reactor, a liquid phase slurry reactor or a liquid phase solution reactor using a heterogeneous catalyst system (such as a Ziegler-Natta catalyst), a homogeneous catalyst system comprising a Group 4 transition metal and a ligand structure (such as a metallocene, a non-metallocene metal center, a heteroaryl, an isovalent aryloxy ether, a phosphinimine, etc.). Combinations of heterogeneous and / or homogeneous catalysts can also be used in a single reactor or dual reactor configuration.

[0019] "Ethylene plastomer / elastomer" is a substantially linear or linear ethylene / α-olefin copolymer containing a homogeneous distribution of short chain branches, which comprises units derived from ethylene and units derived from at least one C3-C 10 The ethylene plastomers / elastomers have a density of 0.854 g / cc to 0.920 g / cc. Non-limiting examples of ethylene plastomers / elastomers include AFFINITY TM Plastomers and elastomers (available from The Dow Chemical Company), EXACT TM Plastomers (available from ExxonMobil Chemical), Tafmer TM (available from Mitsui), Nexlene TM (available from SK Chemicals Co.) and Lucene TM (Available from LG Chem Ltd.).

[0020] "High density polyethylene" (or "HDPE") is a homopolymer of ethylene or ethylene with at least one C4-C 10The HDPE may be a unimodal copolymer or a multimodal copolymer. A "unimodal ethylene copolymer" is an ethylene / α-olefin copolymer having one distinct peak in a gel permeation chromatography (GPC) showing a molecular weight distribution. 10 α-olefin copolymers. "Multimodal ethylene copolymers" are ethylene / C4-C6 copolymers having at least two distinct peaks in a GPC graph showing molecular weight distribution. 10 α-olefin copolymers. Multimodal includes copolymers with two peaks (bimodal) and copolymers with more than two peaks. Non-limiting examples of HDPE include DOW TM High-density polyethylene (HDPE) resin (available from The Dow Chemical Company), ELITE TM Enhanced polyethylene resin (available from The Dow Chemical Company), CONTINUUM TM Bimodal polyethylene resin (available from The Dow Chemical Company), LUPOLEN TM (available from LyondellBasell) and HDPE products from Borealis, Ineos and ExxonMobil.

[0021] As used herein, the term "linear low density polyethylene" (or "LLDPE") refers to a linear ethylene / α-olefin copolymer containing a heterogeneous distribution of short chain branches, which comprises units derived from ethylene and units derived from at least one C3-C 10 Units of α-olefins or C4-C8 α-olefin comonomers. LLDPE is characterized by minimal long chain branching (if any) compared to conventional LDPE. LLDPE has a density of 0.910 g / cc to less than 0.940 g / cc. Non-limiting examples of LLDPE include TUFLIN TM Linear low density polyethylene resin (available from The Dow Chemical Company), DOWLEX TM Polyethylene resin (available from The Dow Chemical Company) and MARLEX TM Polyethylene (available from Chevron Phillips).

[0022] The term "low density polyethylene" (or "LDPE") may also be referred to as "high pressure ethylene polymer" or "highly branched polyethylene" and is an ethylene homopolymer and is typically produced by high pressure free radical polymerization (≥100 MPa (e.g., 100 MPa-400 MPa), tubular reactor or autoclave reactor with a free radical initiator). The density of LDPE resins is typically in the range of 0.915 g / cc to less than 0.940 g / cc. LDPE is distinct from LLDPE.

[0023] A "foam composition" (or "foam") is a polymer composition having a porous structure. In other words, in its natural state and before contact with a blowing agent, the polymer composition has no porous structure, and after contact with a blowing agent and decompression, the polymer composition is a foam composition having a porous structure. The cells may be open cells, closed cells, or a combination thereof. In one embodiment, the cells have a uniform or substantially uniform cell size.

[0024] As used herein, "olefin polymer" or "polyolefin" is a polymer containing more than 50 mole % polymerized olefin monomer (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Non-limiting examples of olefin polymers include ethylene-based polymers and propylene-based polymers.

[0025] "Polymer" is a compound prepared by polymerizing monomers of the same or different types that provide multiple and / or repeating "units" or "monomer units" constituting the polymer in a polymerized form. Therefore, the general term polymer covers the term homopolymer, which is usually used to refer to polymers prepared from only one type of monomer, and the term copolymer, which is usually used to refer to polymers prepared from at least two types of monomers. The general term also covers all forms of copolymers, such as random copolymers, block copolymers, etc. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" represent copolymers prepared by polymerizing ethylene or propylene and one or more other polymerizable α-olefin monomers, respectively, as described above. It should be noted that although polymers are often referred to as being "made of" one or more specific monomers, "based on" a specific monomer or monomer type, "containing" a specific monomer content, etc., in this context, the term "monomer" should be understood to refer to the polymerized remains of a specific monomer, rather than an unpolymerized species. In general, polymers herein refer to "units" based on the polymerized form of the corresponding monomer.

[0026] A "propylene-based polymer" is a polymer containing more than 50 weight percent polymerized propylene monomer (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Propylene polymers include propylene homopolymers and propylene copolymers (meaning units derived from propylene and one or more comonomers). The terms "propylene-based polymer" and "polypropylene" are used interchangeably.

[0027] Test Method

[0028] Foam composition Asker C Hardness Measurements were made on patches of 20 cm (length) x 10 cm (width) x 1-2 cm (thickness) according to ASTM D2240. One sample was tested for each example. Each sample was measured at least three times (with a 5 second delay between each measurement) across the surface of the sample (i.e., at different locations along the sample). The average value was recorded.

[0029] Compression set (C-Set) Measured at 50°C for 6 hours at 50% compression according to ASTM D395 Method B. Two cylindrical foam samples (commonly referred to as "buttons") with a diameter of 29 mm (± 0.5 mm) and a thickness of about 19.5 mm (± 0.5 mm) were tested for each foam sample and the average value was recorded.

[0030] density Measured according to ASTM D792, with results reported in g / cc at 25°C.

[0031] Dynamic Mechanical Analysis (DMA) DMA experiments were performed using a TA Instruments RSA-G2 solid analyzer to measure the storage modulus (G'), loss modulus (G"), and damping ratio (tan δ) of the networks as a function of temperature and recovery under a nitrogen atmosphere. The DMA was operated in tension mode with a frequency of 1 Hz and an oscillating strain of 0.03%. Data were collected from room temperature to 160 °C at a heating rate of 3 °C / min.

[0032] Ball bounce (skin and foam) A 5 / 8" diameter steel ball was dropped from a height of 500 mm onto the plastic block foam skin and foam layer (before and after aging) to determine the % rebound or resilience. The % rebound was calculated as rebound height (mm)*100 / 500.

[0033] Melt Index (MI or I2) (for ethylene-based polymers) is measured according to ASTM D 1238, Condition 190°C / 2.16 kg, wherein the results are reported in grams per 10 minutes (g / 10 min). DETAILED DESCRIPTION

[0034] The present disclosure provides a foam product. In one embodiment, the foam product includes a cross-linked foam composition. The cross-linked foam composition is formed from a starting material, the starting material comprising: a polymer selected from a vinyl polymer, a polar vinyl polymer, and a combination thereof; and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS) methacrylate.

[0035] A. Ethylene polymers

[0036] The crosslinked foam composition is formed from a crosslinkable polymer composition (interchangeably referred to as a "starting material"). The crosslinkable polymer composition comprises an ethylene polymer and / or a polar ethylene polymer. The ethylene polymer may be an ethylene homopolymer, an ethylene / C3-C 10 Alpha-olefin copolymers or ethylene C4-C8 alpha-olefin copolymers. The melt index (MI) of the ethylene polymer is 0.1g / 10min to 100g / 10min, or 1g / 10min to 100g / 10min, or 1g / 10min to 50g / 10min, or 1g / 10min to 25g / 10min, or 1g / 10min to 10g / 10min, or 1g / 10min to 5g / 10min. Non-limiting examples of suitable ethylene polymers include ethylene plastomers / elastomers, high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), ethylene / alpha-olefin multi-block copolymers, and combinations thereof.

[0037] In one embodiment, the ethylene-based polymer is an ethylene plastomer / elastomer.

[0038] In one embodiment, the ethylene-based polymer is HDPE.

[0039] In one embodiment, the ethylene-based polymer is LLDPE.

[0040] In one embodiment, the ethylene-based polymer is LDPE.

[0041] In one embodiment, the ethylene polymer is an ethylene / α-olefin multi-block copolymer. The term "ethylene / α-olefin multi-block copolymer" refers to an ethylene / C4-C8 α-olefin multi-block copolymer composed of ethylene and a copolymerizable C4-C8 α-olefin comonomer (and optional additives) in polymerized form, the polymer being characterized in that multiple blocks or segments of two polymerized monomer units are different in chemical or physical properties, and the blocks are connected (or covalently bonded) in a linear manner, i.e., a polymer containing chemically distinguishable units connected end-to-end relative to the polymerized olefinic functionality. Ethylene / α-olefin multi-block copolymers include block copolymers having two blocks (diblocks) and more than two blocks (multi-blocks). C4-C8 α-olefins are selected from butene, hexene and octene. Ethylene / α-olefin multi-block copolymers do not contain or otherwise do not contain styrene (i.e., do not contain styrene), and / or ethylene aromatic monomers, and / or conjugated dienes. When referring to the amount of "ethylene" or "comonomer" in a copolymer, it is understood that this refers to polymerized units thereof. In some embodiments, the ethylene / α-olefin multi-block copolymer may be represented by the formula: (AB) n ; wherein n is at least 1, preferably an integer greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more, "A" represents a hard block or segment and "B" represents a soft block or segment. Preferably, A and B are connected or covalently bonded in a substantially linear manner, or in a linear manner, relative to a substantially branched or substantially star-shaped manner. In other embodiments, the A blocks and B blocks are randomly distributed along the polymer chain. In other words, the block copolymer generally does not have the following structure: AAA-AA-BBB-BB. In one embodiment, the ethylene / α-olefin multi-block copolymer does not have a third type of block, which comprises one or more different comonomers. In another embodiment, block A and block B each have monomers or comonomers that are substantially randomly distributed within the block. In other words, neither block A nor block B comprises two or more subsegments (or subblocks) of different compositions, such as an end segment having a substantially different composition than the remainder of the block.

[0042] In one embodiment, ethylene comprises most of the mole fraction of the entire ethylene / α-olefin multi-block copolymer, i.e., ethylene comprises at least 50% by weight of the entire ethylene / α-olefin multi-block copolymer. More preferably, ethylene comprises at least 60% by weight, at least 70% by weight, or at least 80% by weight, and the substantial remainder of the entire ethylene / α-olefin multi-block copolymer comprises C4-C8 α-olefin comonomers. In one embodiment, the ethylene / α-olefin multi-block copolymer contains 50% to 90% by weight of ethylene, or 60% to 85% by weight of ethylene, or 65% to 80% by weight of ethylene. For a variety of ethylene / octene multi-block copolymers, the composition comprises an ethylene content greater than 80% by weight of the entire ethylene / octene multi-block copolymer and an octene content of 10% to 15% by weight, or 15% to 20% by weight of the entire multi-block copolymer.

[0043] Ethylene / alpha-olefin multi-block copolymers include various amounts of "hard" segments and "soft" segments. "Hard" segments are blocks of polymerized units, wherein based on the weight of the polymer, ethylene is present in an amount greater than 90 wt %, or 95 wt %, or greater than 95 wt %, or greater than 98 wt %, up to 100 wt %. In other words, by the weight of the polymer, the comonomer content (except the monomer content of ethylene) in the hard segments is less than 10 wt %, or 5 wt %, or less than 5 wt %, or less than 2 wt %, and can be as low as zero. In some embodiments, the hard segments include all or substantially all units derived from ethylene. "Soft" segments are blocks of polymerized units, in which, by the weight of the polymer, the comonomer content (the content of monomers other than ethylene) is greater than 5 wt %, or greater than 8 wt %, greater than 10 wt %, or greater than 15 wt %. In one embodiment, the comonomer content in the soft segments is greater than 20 wt%, greater than 25 wt%, greater than 30 wt%, greater than 35 wt%, greater than 40 wt%, greater than 45 wt%, greater than 50 wt%, or greater than 60 wt% and can be as high as 100 wt%.

[0044] The soft segment can be present in ethylene / alpha-olefin multi-block copolymers from 1% to 99% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer, or from 5% to 95% by weight, 10% to 90% by weight, 15% to 85% by weight, 20% to 80% by weight, 25% to 75% by weight, 30% to 70% by weight, 35% to 65% by weight, 40% to 60% by weight, or 45% to 55% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer. On the contrary, the hard segment can be present in a similar range. The soft segment weight percentage and the hard segment weight percentage can be calculated based on the data obtained from DSC or NMR. Such methods and calculations are disclosed in, for example, USP 7,608,668, entitled "Ethylene / α-Olefin Block Inter-Polymers", filed on March 15, 2006 in the name of Colin L.P. Shan, Lonnie Hazlitt et al. and assigned to Dow Global Technologies Inc., the disclosure of which is incorporated herein by reference in its entirety. Specifically, the hard segment weight percentage and the soft segment weight percentage and the comonomer content can be determined as described in columns 57 to 63 of USP 7,608,668.

[0045] The ethylene / α-olefin multi-block copolymer comprises two or more chemically distinct regions or segments (referred to as "blocks") that are linked (or covalently bonded) in a linear manner, i.e., they contain chemically distinguishable units that are linked end-to-end with respect to the polymerized olefinic functionality, rather than in a pendant or grafted manner. In one embodiment, the blocks differ in the amount or type of comonomer incorporated, density, amount of crystallinity, crystallite size attributable to polymers of such compositions, type or degree of stereoisomerism (isotactic or syndiotactic), regioregularity or regioirregularity, amount of branching (including long chain branching or hyperbranching), uniformity, or any other chemical or physical characteristic. Compared to prior art block interpolymers, including those produced by sequential monomer addition, stereolabile catalysts, or anionic polymerization techniques, the inventive ethylene / α-olefin multi-block copolymers are characterized by a unique distribution of polymer polydispersity (PDI or Mw / Mn or MWD), polydisperse block length distribution, and / or polydisperse block number distribution, which, in one embodiment, is due to the effect of one or more shuttling agents in combination with various catalysts used in their preparation.

[0046] In one embodiment, the ethylene / α-olefin multi-block copolymer is produced in a continuous process and has a polydispersity index (Mw / Mn) of 1.7 to 3.5, or 1.8 to 3, or 1.8 to 2.5, or 1.8 to 2.2. When prepared in a batch or semi-batch process, the ethylene / α-olefin multi-block copolymer has a Mw / Mn of 1.0 to 3.5, or 1.3 to 3, or 1.4 to 2.5, or 1.4 to 2.

[0047] In addition, the ethylene / α-olefin multi-block copolymer has a PDI (or Mw / Mn) that fits the Schultz-Flory distribution rather than the Poisson distribution. The ethylene / α-olefin multi-block copolymer of the present invention has both a polydisperse block distribution and a polydisperse distribution of block sizes. This results in the formation of a polymer product with improved and distinguishable physical properties. The theoretical benefits of a polydisperse block distribution have been previously described in Potemkin, Physical Review E( Physical Review E ) (1998) 57(6), pp. 6902-6912 and Dobrynin, Journal of Chemical Physics ( J.Chem.Phvs.)》 The theoretical benefits of polydisperse block distributions are modeled and discussed in (1997) 107(21), pp. 9234-9238.

[0048] In one embodiment, the ethylene / α-olefin multi-block copolymers of the present invention have a most probable distribution of block lengths.

[0049] In another embodiment, the ethylene / α-olefin multi-block copolymers of the present disclosure, especially those copolymers made in a continuous solution polymerization reactor, have the most probable distribution of block lengths. In one embodiment of the present disclosure, the ethylene / α-olefin multi-block copolymers are defined as having:

[0050] (A) an Mw / Mn of about 1.7 to about 3.5, at least one melting point Tm in degrees Celsius and a

[0051] / density d in cubic centimeters, where the values ​​of Tm and d correspond to the following relationship:

[0052] Tm>-2002.9+4538.5(d)-2422.2(d) 2 , and / or

[0053] (B) an Mw / Mn of from about 1.7 to about 3.5, and is characterized by a heat of fusion, DH, in J / g, and a differential, DT, in degrees Celsius, defined as the temperature difference between the tallest DSC peak and the tallest Crystallization Analysis Separation ("CRYSTAF") peak, wherein the numerical values ​​of DT and DH have the following relationship:

[0054] For DH greater than zero and up to 130 J / g, DT>-0.1299DH+62.81

[0055] For DH greater than 130 J / g, DT ≥ 48 °C

[0056] wherein at least 5% of the cumulative polymer is used to determine the CRYSTAF peak, and if less than 5% of the polymer has an identifiable CRYSTAF peak, then the CRYSTAF temperature is 30°C; and / or

[0057] (C) an elastic recovery Re in percent measured at 300% stress and 1 cycle with a compression molded ethylene / α-olefin interpolymer film, and a density d in grams per cubic centimeter, wherein when the ethylene / α-olefin interpolymer is substantially free of a crosslinked phase, the values ​​of Re and d satisfy the following relationship:

[0058] Re>1481-1629(d); and / or

[0059] (D) having a molecular fraction eluting between 40°C and 130°C when fractionated using TREF, characterized in that said fraction has a molar comonomer content at least 5% higher than an equivalent comparable random ethylene interpolymer fraction eluting between the same temperatures, wherein said comparable random ethylene interpolymer has the same comonomers and has a melt index, density, and molar comonomer content (based on the whole polymer) within 10% of that of an interpolymer of ethylene / α-olefin; and / or

[0060] (E) has a storage modulus G'(25°C) at 25°C and a storage modulus G' at 100°C

[0061] (100°C), wherein the ratio of G'(25°C) to G'(100°C) is in the range of 1:1 to 9:1.

[0062] The ethylene / α-olefin multi-block copolymer may also have:

[0063] (F) a molecular fraction eluting between 40°C and 130°C when fractionated using TREF, characterized in that the block index of the fraction is at least 0.5 and at most 1, and the molecular weight distribution Mw / Mn is greater than 1.3; and / or

[0064] (G) The average block index is greater than zero and at most 1.0, and the molecular weight distribution Mw / Mn is greater than 1.3.

[0065] It should be understood that the ethylene / α-olefin multi-block copolymer may have one, some, all or any combination of properties (A)-(G). The block index may be determined as described in detail in USP 7,608,668, which is incorporated herein by reference for the purpose. Analytical methods for determining properties (A) to (G) are disclosed, for example, in USP 7,608,668, column 31, line 26 to column 35, line 44, which is incorporated herein by reference for the purpose.

[0066] In one embodiment, the ethylene / α-olefin multi-block copolymer has hard segments and soft segments, is free of styrene, consists solely of (i) ethylene and (ii) a C4-C8 α-olefin or a C8 α-olefin (and optional additives), and is defined as having a Mw / Mn of 1.7 to 3.5, at least one melting point Tm in degrees Celsius, and a density d in grams / cubic centimeter, wherein the numerical values ​​of Tm and d correspond to the following relationship:

[0067] Tm>-2002.9+4538.5(d)-2422.2(d) 2 ,

[0068] wherein the density d is 0.850 g / cc, or 0.860 g / cc, or 0.870 g / cc to 0.875 g / cc, or 0.877 g / cc, or 0.880 g / cc, or 0.890 g / cc; and the melting point Tm is 110°C, or 115°C, or 120°C to 125°C, or 130°C, or 135°C.

[0069] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / 1-octene multi-block copolymer (consisting only of ethylene and octene comonomers) and has one, some or all of the following characteristics:

[0070] (i) an Mw / Mn of from 1.7, or 1.8 to 2.2, or 2.5, or 3.5; and / or

[0071] (ii) a density of 0.860 g / cc, or 0.865 g / cc to 0.870 g / cc, or 0.877 g / cc, or 0.880 g / cc; and / or

[0072] (iii) a melting point Tm of 115°C, or 118°C, or 119°C, or 120°C to 120°C, or 123°C, or 125°C; and / or

[0073] (iv) a melt index (MI) of 0.1 g / 10 min, or 0.5 g / 10 min to 1.0 g / 10 min, or 2.0 g / 10 min, or 5 g / 10 min, or 10 g / 10 min; and / or

[0074] (v) 50 to 85 weight percent soft segments and 40 to 15 weight percent hard segments (based on the total weight of the ethylene / octene multi-block copolymer); and / or

[0075] (vi) 10 mol%, or 13 mol%, or 14 mol%, or 15 mol% to 16 mol%, or 17 mol%, or 18 mol%, or 19 mol%, or 20 mol% octene in the soft segment;

[0076] and / or

[0077] (vii) 0.5 mol%, 1.0 mol%, 2.0 mol%, or 3.0 mol% in the hard segment

[0078] to 4.0 mol%, or 5 mol%, or 6 mol%, or 7 mol%, or 9 mol% of octene; and / or

[0079] (viii) 300% min at 21°C as measured according to ASTM D 1708 ·1 50%, or 60% to 70%, or 80%, or 90% elastic recovery (Re) at deformation rate; and

[0080] / or

[0081] (ix) Polydispersity distribution of blocks and polydispersity distribution of block sizes (hereinafter referred to as multi-block copolymer properties (i) to (ix)).

[0082] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / octene multi-block copolymer. The ethylene / octene multi-block copolymer is marketed under the trade name INFUSE TM Sold and available from The Dow Chemical Company, Midland, Michigan, USA.

[0083] Ethylene / α-olefin multi-block copolymers can be produced via a chain shuttling process as described in USP 7,858,706, which is incorporated herein by reference. Specifically, suitable chain shuttling agents and related information are listed in column 16, line 39 to column 19, line 44. Suitable catalysts are described in column 19, line 45 to column 46, line 19 and suitable co-catalysts are described in column 46, line 20 to column 51, line 28. The process is described throughout the literature, but especially in column 51, line 29 to column 54, line 56. The process is also described, for example, in the following: USP 7,608,668; USP 7,893,166; and USP 7,947,793.

[0084] The ethylene / α-olefin multi-block copolymer may include more than one ethylene / α-olefin multi-block copolymer.

[0085] B. Polar vinyl polymers

[0086] The foam article (and / or crosslinkable polymer composition) comprises ethylene polymers and / or polar ethylene polymers. As used herein, "polar ethylene polymers" are ethylene polymers composed of (i) ethylene monomers, (ii) comonomers containing heteroatoms, and (iii) optional terionomers (which may or may not contain heteroatoms). In other words, polar ethylene polymers are not hydrocarbons. The melt index (MI) of polar ethylene polymers is 0.1 g / 10min to 100 g / 10min, or 1 g / 10min to 100 g / 10min, or 1 g / 10min to 50 g / 10min, or 1 g / 10min to 25 g / 10min, or 1 g / 10min to 10 g / 10min, or 1 g / 10min to 5 g / 10min. Non-limiting examples of comonomers having heteroatoms include carbon monoxide, carboxylic acids, esters, alkyl acrylates having 1 to 30 carbon atoms, methacrylates having 1 to 30 carbon atoms, vinyl siloxanes having 1 to 16 carbon atoms, and halogens. Non-limiting examples of suitable polar vinyl polymers include ethylene / carboxylic acid copolymers and ionomers partially neutralized with metal salts derived therefrom, ethylene / acrylic acid copolymers (EAA), ethylene / methacrylic acid copolymers (EMAA), ethylene / vinyl (trimethoxy) silane copolymers (EVTMS), ethylene / vinyl acetate copolymers (EVA), ethylene / methyl acrylate (EMA), ethylene / ethyl acrylate copolymers (EEA), ethylene / butyl acrylate copolymers (EBA), ethylene / carbon monoxide (ECO), ethylene / glycidyl methacrylate (E / GMA), ethylene / methyl methacrylate copolymers, ethylene / butyl methacrylate copolymers, ethylene / stearyl acrylate copolymers, ethylene / stearyl methacrylate copolymers, ethylene / octyl acrylate copolymers, ethylene / 2-ethylhexyl acrylate copolymers, ethylene / dodecyl acrylate copolymers, polyvinyl dichloride (PVCD), ethylene / maleic anhydride copolymers (EMAH), polyvinyl chloride (PVC), and combinations thereof. Additional non-limiting examples of terpolymers include ethylene / carboxylic acid / acrylate terpolymers and partially neutralized ionomers with metal salts derived therefrom, ethylene / methyl acrylate / vinyl (trimethoxy) silane terpolymers (EMAVTMS), ethylene / ethyl acrylate / vinyl (trimethoxy) silane terpolymers (EEAVTMS), ethylene / butyl acrylate / vinyl (trimethoxy) silane terpolymers (EBAVTMS), ethylene / methyl acrylate / glycidyl methacrylate (EMAGMA), ethylene / butyl acrylate / glycidyl methacrylate (EBAGMA), ethylene / vinyl acetate / maleic anhydride terpolymers (EEAMAH), ethylene ethyl acrylate / maleic anhydride (EEAMAH) terpolymers, and combinations thereof.

[0087] In one embodiment, the polar vinyl polymer is an ethylene / vinyl acetate copolymer.

[0088] D. Free Radical Initiator

[0089] The foamed article is formed from a crosslinkable composition consisting of a vinyl polymer and / or a polar vinyl polymer, a free radical initiator, BiTEMPS methacrylate, and optional additives. The crosslinkable composition includes a free radical initiator.

[0090] The amount of the free radical initiator in the crosslinkable polymer composition or foam article may be from about greater than 0 wt % to about 10 wt %, from about 0.1 wt % to about 7.5 wt %, or from about 1 wt % to about 5 wt %, based on the weight of the vinyl polymer and / or polar vinyl polymer or polymer blend.

[0091] Non-limiting examples of suitable free radical initiators include peroxides, phenols, azides, aldehyde-amine reaction products, substituted ureas, substituted guanidines; substituted xanthates; substituted dithiocarbamates; sulfur-containing compounds such as thiazoles, sulfenamides, thiuram disulfides, p-quinonedioxime, dibenzo-p-quinonedioxime, sulfur, imidazoles; silanes, and combinations thereof.

[0092] In one embodiment, the free radical initiator is an organic peroxide. In certain embodiments, the organic peroxide is a molecule containing carbon atoms, hydrogen atoms and two or more oxygen atoms and having at least one -OO- group, provided that when there are more than one -OO- groups, each -OO- group is indirectly bonded to another -OO- group via one or more carbon atoms; or a collection of such molecules.

[0093] The organic peroxide may be a dialkyl peroxide. The organic peroxide may be a monoperoxide of the formula RO-OO-RO, wherein each RO is independently (C1-C 20 )alkyl or (C6-C 20 ) aryl. Each (C1-C 20 ) alkyl groups are independently unsubstituted or substituted with 1 or 2 (C6-C 12 ) aryl group. Each (C6-C 20 ) aryl groups are unsubstituted or substituted with 1 to 4 (C1-C 10 Alternatively, the organic peroxide may be a diperoxide of the formula RO-OOROO-RO, wherein R is a divalent hydrocarbon group, such as (C2-C 10 ) alkylene, (C3-C 10)cycloalkylene or phenylene, and each RO is as defined above.

[0094] The peroxide may be a peroxycarbonate. Suitable peroxycarbonate-type peroxides include isopropyl peroxycarbonate; tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, tert-butyl peroxyisopropyl carbonate, tert-butyl peroxy-3,5,5-trimethylhexanoate. The peroxide may be a diacyl peroxide. Non-limiting examples of suitable acyl peroxide-type peroxides include dilauroyl peroxide; benzoyl peroxide; didecanoyl peroxide;

[0095] The peroxide may be a peroxyester. Non-limiting examples of suitable peroxyester-type peroxides include tert-butyl peroxybenzoate, tert-butyl peroxyacetate, tert-amyl peroxybenzoate, tert-butyl peroxy-3,5,5-trimethylhexanoate; tert-butyl peroxyisobutyrate; tert-butyl peroxydiethylacetate; tert-butyl peroxy-2-ethylhexanoate; tert-amyl peroxy-2-ethylhexanoate; 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate; 2,5-dimethyl-2,5-di(2-ethylhexanoyl peroxy)hexane. The peroxide may be a peroxyketal. Non-limiting examples of suitable peroxyketal-type peroxides include 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane; 1,1-di(tert-butylperoxy)cyclohexane; 1,1-di(tert-amylperoxy)cyclohexane.

[0096] The peroxide may be a cyclic ketone peroxide. Non-limiting examples of suitable cyclic ketone peroxides include 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane.

[0097] Non-limiting examples of suitable organic peroxides include bis(1,1-dimethylethyl)peroxide; bis(1,1-dimethylpropyl)peroxide; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexane; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexyne; 4,4-bis(1,1-dimethylethylperoxy)pentanoic acid; butyl ester; 1,1-bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane; benzoyl peroxide; tert-butyl peroxybenzoate; di-tert-amyl peroxide ( "DTAP"); bis(α-tert-butylperoxyisopropyl)benzene ("BIPB"); isopropylcumyl tert-butyl peroxide; tert-butylcumyl peroxide; di-tert-butyl peroxide; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexyne-3,1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane; isopropylcumylcumyl peroxide; butyl 4,4-di(tert-butylperoxy)valerate; di(isopropylcumyl) peroxide; diisopropylbenzene peroxide, and combinations thereof. Non-limiting examples of suitable commercially available organic peroxides include Benzene, Aquatek, and Benzene from AkzoNobel. and from ARKEMA

[0098] In one embodiment, the free radical initiator is dicumyl peroxide and / or bis(α-tert-butyl-isopropylperoxy)benzene. In some embodiments, the foam or crosslinkable composition disclosed herein may include a crosslinking aid. As used herein, a "crosslinking aid" is a compound that promotes crosslinking; for example, by helping to establish a higher concentration of reactive sites and / or helping to reduce the chance of harmful free radical side reactions. Crosslinking aids include, but are not limited to, triallyl cyanurate (TAC), triallyl phosphate (TAP), triallyl isocyanurate (TAIC), 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane (vinyl D4), 2,4,6-trimethyl-2,4,6-trivinyl-1,3,5,2,4,6-cyclotrisiloxane (vinyl D3), 2,4,6,8,10-pentamethyl-2,4,6,8,10-pentavinyl-1,3,5,7,9,2,4,6,8,10-cyclopentasiloxane (vinyl D5), dipentaerythritol pentaacrylate, and trimethylolpropane triacrylate, triallyl trimellitate. ; N,N,N',N',N",N"-hexaallyl-1,3,5-triazine-2,4,6-triamine; triallyl orthoformate; pentaerythritol triallyl ether; triallyl citrate; triallyl aconitate; trimethylolpropane triacrylate; trimethylolpropane trimethacrylate; ethoxylated bisphenol A dimethacrylate; 1,6-hexanediol diacrylate; pentaerythritol tetraacrylate; dipentaerythritol pentaacrylate; tris(2-hydroxyethyl)isocyanurate triacrylate; propoxylated glycerol triacrylate; polybutadiene having a 1,2-vinyl content of at least 50% by weight; trivinylcyclohexane; and mixtures of any two or more thereof.

[0099] Alternatively, crosslinking of the foam or crosslinkable polymer composition disclosed herein can be achieved by using radiation. Non-limiting examples of suitable radiation include electron beams or beta rays, gamma rays, X-rays or neutron rays. It is believed that radiation activates crosslinking by generating free radicals in the polymer, which can then combine and crosslink. In some embodiments, the foam or crosslinkable composition is not crosslinked by radiation.

[0100] The radiation dose generally depends on a variety of factors. Suitable radiation levels are based on the thickness and geometry of the article to be irradiated, and the properties of the ethylene polymer and / or polar ethylene polymer or polymer blend, such as molecular weight, molecular weight distribution, comonomer content, crosslinking enhancement aids, the presence of additives (e.g., oil), etc. Typically, the dose does not exceed the dose required to achieve the desired level of crosslinking. In some embodiments, according to ASTM D-2765-84 Method A, the dose results in more than 5% gel in the foam.

[0101] In some embodiments, a dual cure system may be effectively employed, comprising at least two activation methods selected from free radical initiators and radiation. For example, it may be desirable to use a peroxide free radical initiator in combination with a silane free radical initiator, a peroxide free radical initiator in combination with radiation, a sulfur-containing free radical initiator in combination with a silane free radical initiator, and the like.

[0102] It is contemplated that the vinylic polymer and / or polar vinylic polymer may be blended with other polymers and polyolefins prior to crosslinking.

[0103] E.BiTEMPS Methacrylate

[0104] The foam article and / or the crosslinkable polymer composition comprises 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide, interchangeably referred to as "BiTEMPS methacrylate" or "BiTEMPS" or "BiT." BiTEMPS methacrylate disulfide has the following structure 1.

[0105]

[0106] In one embodiment, the crosslinkable polymer composition comprises:

[0107] 70 wt % to 98.5 wt %, or 77 wt % to 98.5 wt % of ethylene polymers and / or polar ethylene polymers;

[0108] 0.5 to 10 wt%, or 0.5 to 5 wt%, 0.5 to 3.0 wt%, or 0.5 to 1.5 wt%, or 1.5 to 3.0 wt% of a free radical initiator, which is an organic peroxide (e.g., dicumyl peroxide); and

[0109] 1 wt % to 20 wt %, or 1 wt % to 15 wt %, or 3 wt % to 20 wt %, or 3 wt % to 10 wt % of BiTEMPS methacrylate disulfide. It is understood that the aggregate of the vinyl polymer (and / or polar vinyl polymer), free radical initiator, and BiTEMPS methacrylate disulfide (and optional additives) totals 100 wt % of the crosslinkable polymer composition.

[0110] The present disclosure provides a cross-linked composition. The cross-linkable polymer composition is melt blended at a temperature of 70°C to 250°C, or 80°C to 200°C, or 90°C to 180°C, or 100°C to 160°C, or 130°C to 250°C, or 140°C to 200°C, or 150°C to 180°C, or 160°C to 175°C to initiate a cross-linking reaction and form a cross-linked composition. In one embodiment, the cross-linked composition comprises an ethylene polymer and / or a polar ethylene polymer and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). The cross-linked composition contains a disulfide bond formed by BiTEMPS methacrylate through a cross-linking reaction, and the disulfide bond has the following structure 2.

[0112]

[0113] The term (and structure) "P" in Structure 2 above refers to the chains of polymerized ethylene (and optional comonomers) of the ethylene polymer. The ethylene polymer (and / or polar ethylene polymer) of the crosslinked composition can be any ethylene polymer (and / or polar ethylene polymer) having a MI of 0.1 g / 10 min to 100 g / 10 min as previously disclosed herein. Non-limiting examples of suitable ethylene polymers (and / or polar ethylene polymers) include ethylene plastomers / elastomers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), ethylene / α-olefin multi-block copolymers, ethylene vinyl acetate, and combinations thereof.

[0114] In one embodiment, the vinyl polymer and / or the polar vinyl polymer (interchangeably referred to as a "(polar) vinyl polymer") is a virgin (polar) vinyl polymer. As used herein, a "virgin (polar) vinyl polymer" is a (polar) vinyl polymer that has not yet undergone a crosslinking reaction. In other words, the term "virgin (polar) vinyl polymer" refers to the (polar) vinyl polymer present in the crosslinked composition before the (polar) vinyl polymer is crosslinked with BiTEMPS methacrylate. The virgin (polar) vinyl polymer is the (polar) vinyl polymer before crosslinking, the crosslinked composition comprising the same (polar) vinyl polymer that is virgin but now crosslinked with BiTEMPS methacrylate. In this way, the virgin (polar) vinyl polymer is used as a benchmark for evaluating the performance of the crosslinked composition. The crosslinked composition has

[0115] (i) a storage modulus value G' at 140°C that is greater than the storage modulus value G' of the virgin ethylene polymer at 140°C;

[0116] (ii) a tan δ value at 60°C that is less than the tan δ value of the virgin ethylene polymer at 60°C;

[0117] as well as

[0118] (iii) a tan δ value at 140°C that is less than the tan δ value of the native ethylene polymer at 140°C.

[0119] In one embodiment, the crosslinking composition comprises 80 to 97 wt% of the ethylenic polymer and 3 to 20 wt% of the BiTEMPS methacrylate, the aggregate of the ethylenic polymer and the BiTEMPS methacrylate (and optional additives) totaling 100 wt% of the crosslinking composition.

[0120] F. Blend Components

[0121] In one embodiment, the crosslinkable composition and / or the crosslinked composition comprises a blend component. Non-limiting examples of suitable blend components include polyolefins (e.g., polyethylene other than ethylene polymers crosslinked with BiTEMPS methacrylate and polypropylene), polymers (e.g., polystyrene, ABS, SBS, etc.), and combinations thereof. Non-limiting examples of suitable polyolefins include polyethylene; polypropylene; polybutene (e.g., polybutene-1); polypentene-1; polyhexene-1; polyoctene-1; polydecene-1; poly-3-methylbutene-1; poly-4-methylpentene-1; polyisoprene; polybutadiene; poly-1,5-hexadiene; interpolymers derived from olefins; interpolymers derived from olefins and other polymers such as polyvinyl chloride, polystyrene, polyurethane, etc.; and mixtures thereof.

[0122] In one embodiment, the polyolefin is a homopolymer such as polyethylene, polypropylene, polybutene, polypentene-1, poly-3-methylbutene-1, poly-4-methylpentene-1, polyisoprene, polybutadiene, poly-1,5-hexadiene, polyhexene-1, polyoctene-1, and polydecene-1.

[0123] Non-limiting examples of polyethylenes suitable as blend components (other than ethylene polymers crosslinked with BITEMPS methacrylate) include ultra low density polyethylene (ULDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), high molecular weight high density polyethylene (HMW-HDPE), ultra high molecular weight polyethylene (UHMW-PE), and combinations thereof. Non-limiting examples of polypropylenes include low density polypropylene (LDPP), high density polypropylene (HDPP), high melt strength polypropylene (HMS-PP), and combinations thereof. In one embodiment, the blend component is high melt strength polypropylene (HMS-PP), low density polyethylene (LDPE), or combinations thereof.

[0124] G. Additives

[0125] The crosslinkable composition and / or crosslinked composition may contain one or more optional additives. Non-limiting examples of suitable additives include grafting initiators, crosslinking catalysts, blowing agents, blowing agent activators (e.g., zinc oxide, zinc stearate, etc.), auxiliary agents (e.g., triallyl cyanurate), plasticizers, processing oils, processing aids, carbon black, colorants or pigments, stability control agents, nucleating agents, fillers, antioxidants, acid scavengers, ultraviolet (UV) stabilizers, flame retardants, lubricants, processing aids, extrusion aids, and combinations thereof. When present, the total amount of additives may be greater than 0% to 80%, or 0.001% to 70%, or 0.01% to 60%, or 0.1% to 50%, or 0.1% to 40%, or 0.1% to 20%, or 0.1% to 10%, or 0.1% to 5% of the total weight of the composition.

[0126] In one embodiment, the crosslinkable composition and / or the crosslinked composition comprises an antioxidant. Non-limiting examples of suitable antioxidants include aromatic amines or hindered amines, such as alkyl diphenylamines, phenyl-α-naphthylamines, alkyl or aralkyl substituted phenyl-α-naphthylamines, alkylated p-phenylenediamines, tetramethyl diamino diphenylamine, etc.; phenols such as 2,6-di-tert-butyl-4-methylphenol; 1,3,5-trimethyl-2,4,6-tris (3',5,-di-tert-butyl-4-hydroxybenzyl) benzene; tetrakis [(methylene (3,5-di-tert-butyl-4-hydroxyhydrocinnamate)] methane (e.g., IRGANOX TM 1010, available from Ciba Geigy, New York); acryloyl-modified phenol; octadecyl 3,5-di-tert-butyl-4-hydroxycinnamate (e.g., IRGANOX TM1076, commercially available from Ciba Geigy); phosphites and phosphonites; hydroxylamines; benzofuranone derivatives; and combinations thereof. When used, the amount of antioxidant in the composition can be from greater than 0% to 5% by weight, or from 0.0001% to 2.5% by weight, or from 0.001% to 1% by weight, or from 0.001% to 0.5% by weight of the total weight of the composition.

[0127] In one embodiment, the crosslinkable composition and / or the crosslinked composition comprises a UV stabilizer. Non-limiting examples of suitable UV stabilizers include benzophenones, benzotriazoles, aryl esters, oxanilides, acrylates, formamidines, carbon black, hindered amines, nickel quenchers, hindered amines, phenolic antioxidants, metal salts, zinc compounds, and combinations thereof. When used, the amount of the UV stabilizer may be greater than 0% to 5% by weight, or 0.01% to 3% by weight, or 0.1% to 2% by weight, or 0.1% to 1% by weight of the total weight of the composition.

[0128] In one embodiment, the crosslinkable composition and / or the crosslinked composition include a colorant or pigment. The non-limiting example of suitable colorants or pigments includes inorganic pigments, for example, metal oxides such as iron oxide, zinc oxide and titanium dioxide, mixed metal oxides, carbon black, organic pigments such as anthraquinone, anthraquinone, azo and monoazo compounds, arylamide, benzimidazolone, BONA lake, diketopyrrolopyrrole, dioxazine, disazo compounds, diarylide compounds, flavanone, indanthrone, isoindolinone, isoindolinone, metal complex, monoazo salt, naphthol, b-naphthol, naphthol AS, naphthol lake, perylene, perylone, phthalocyanine, pyranthrone, quinacridone and quinophthalone, and combinations thereof. When used, the amount of colorant or pigment in the composition can be greater than 0% by weight to 10% by weight, or 0.1% by weight to 5% by weight, or 0.25% by weight to 2% by weight of the total weight of the composition.

[0129] In one embodiment, the crosslinkable composition and / or the crosslinked composition comprises a filler. Non-limiting examples of suitable fillers include talc, calcium carbonate, chalk, calcium sulfate, clay, kaolin, silica, glass, fumed silica, mica, wollastonite, feldspar, aluminum silicate, calcium silicate, aluminum oxide, hydrated aluminum oxide such as aluminum oxide trihydrate, glass microspheres, ceramic microspheres, thermoplastic microspheres, barite, wood flour, glass fiber, carbon fiber, marble powder, cement powder, magnesium oxide, magnesium hydroxide, antimony oxide, zinc oxide, barium sulfate, titanium dioxide, titanates, and combinations thereof.

[0130] In one embodiment, the filler is barium sulfate, talc, calcium carbonate, silicon dioxide, glass, glass fiber, aluminum oxide, titanium dioxide or a mixture thereof. In another embodiment, the filler is talc, calcium carbonate, barium sulfate, glass fiber or a mixture thereof. When used, the amount of filler in the composition can be greater than 0% to 80% by weight, or 0.1% to 60% by weight, or 0.5% to 40% by weight, or 1% to 30% by weight, or 10% to 40% by weight of the total weight of the composition.

[0131] In one embodiment, the crosslinkable composition and / or the crosslinked composition comprises a lubricant. Non-limiting examples of suitable lubricants include fatty alcohols and dicarboxylic acid esters thereof, fatty acid esters of short-chain alcohols, fatty acids, fatty acid amides, metal soaps, oligomeric fatty acid esters, fatty acid esters of long-chain alcohols, montan wax, polyethylene wax, polypropylene wax, natural and synthetic paraffin waxes, fluoropolymers, and combinations thereof. When used, the amount of lubricant in the composition may be greater than 0% to 5% by weight, or 0.1% to 4% by weight, or 0.1% to 3% by weight of the total weight of the composition.

[0132] In one embodiment, the crosslinkable composition and / or the crosslinked composition include an antistatic agent. Non-limiting examples of suitable antistatic agents include conductive fillers (e.g., carbon black, metal particles and other conductive particles), fatty acid esters (e.g., glyceryl monostearate), ethoxylated alkylamines, diethanolamine, ethoxylated alcohols, alkyl sulfonates, alkyl phosphates, quaternary ammonium salts, alkyl betaines, and combinations thereof. When used, the amount of the antistatic agent in the composition may be greater than 0% to 5% by weight, or 0.01% to 3% by weight, or 0.1% to 2% by weight of the total weight of the composition.

[0133] H. Foam products

[0134] In one embodiment, the crosslinkable polymer composition and / or the crosslinked composition comprises a blowing agent. The blowing agent is used to foam the crosslinked composition. The blowing agent suitable for preparing the foam disclosed herein may include, but is not limited to, inorganic blowing agents, organic blowing agents, chemical blowing agents, and combinations thereof.

[0135] Based on the weight of the ethylene polymer and / or polar ethylene polymer or polymer blend, the amount of blowing agent in the crosslinkable polymer composition disclosed herein can be from about 0.1 wt % to about 20 wt %, from about 0.1 wt % to about 10 wt %, or from about 0.1 wt % to about 5 wt %. In other embodiments, the amount of blowing agent is from about 0.2 mol / kg to about 5.0 mol / kg of interpolymer or polymer blend, from about 0.5 mol / kg to about 3.0 mol / kg of interpolymer or polymer blend, or from about 1.0 mol / kg to about 2.50 mol / kg of interpolymer or polymer blend.

[0136] Non-limiting examples of suitable blowing agents include inorganic physical blowing agents such as air, argon, nitrogen, carbon dioxide, helium, oxygen and neon, and organic physical blowing agents such as aliphatic hydrocarbons, for example, propane, n-butane, isobutane, n-pentane, isopentane and n-hexane; alicyclic hydrocarbons, for example, cyclohexane and cyclopentane; halogenated hydrocarbons, for example, chlorofluoromethane, trifluoromethane, 1,1-difluoroethane, 1,1,1,2-tetrafluoroethane, methyl chloride, ethyl chloride and dichloromethane; and dialkyl ethers, for example, dimethyl ether, diethyl ether and methyl ethyl ether.

[0137] The limiting examples of suitable organic blowing agents include aliphatic hydrocarbons with 1-6 carbon atoms, aliphatic alcohols with 1-3 carbon atoms, and fully and partially halogenated aliphatic hydrocarbons with 1-4 carbon atoms. The limiting examples of suitable aliphatic hydrocarbons include methane, ethane, propane, n-butane, isobutane, n-pentane, isopentane, neopentane, etc. The limiting examples of suitable aliphatic alcohols include methanol, ethanol, n-propyl alcohol, and isopropyl alcohol. The limiting examples of suitable fully and partially halogenated aliphatic hydrocarbons include fluorocarbons, chlorocarbons, and chlorofluoro compounds. Non-limiting examples of suitable fluorocarbons include methyl fluoride, perfluoromethane, ethyl fluoride, 1,1-difluoroethane (HFC152a), 1,1,1-trifluoroethane (HFC-143a), 1,1,1,2-tetrafluoroethane (HFC-134a), pentafluoroethane, difluoromethane, perfluoroethane, 2,2-difluoropropane, 1,1,1-trifluoropropane, perfluoropropane, dichloropropane, difluoropropane, perfluorobutane, and perfluorocyclobutane. Non-limiting examples of suitable partially halogenated chlorocarbons and chlorofluoro compounds include methyl chloride, methylene chloride, ethyl chloride, 1,1,1-trichloroethane, 1,1-dichloro-1-fluoroethane (HCFC-141b), 1-chloro-1,1-difluoroethane (HCFC-142b), 1,1-dichloro-2,2,2-trifluoroethane (HCFC-123), and 1-chloro-1,2,2,2-tetrafluoroethane (HCFC-124). Non-limiting examples of suitable fully halogenated chlorofluoro compounds include trichloromonofluoromethane (OPOI 1), dichlorodifluoromethane (CFO-12), trichlorotrifluoroethane (CFO-113), 1,1,1-trifluoroethane, pentafluoroethane, dichlorotetrafluoroethane (CFO-114), chloroheptafluoropropane, and dichlorohexafluoropropane.

[0138] Non-limiting examples of suitable chemical blowing agents include azodicarbonamide, azobisisobutyronitrile, benzenesulfonylhydrazide, 4,4-hydroxybenzenesulfonylsemicarbazide, p-toluenesulfonylsemicarbazide, barium azodicarboxylate, N,N'-dimethyl-N,N'-dinitrosoterephthalamide, and trihydrazinotriazine.

[0139] The ingredients of the foam, ie, the polymer component, BITEMPS methacrylate, blowing agent and free radical initiator, and optional additives, may be mixed or blended. Non-limiting examples of suitable blending methods include melt blending, solvent blending, extrusion, and the like.

[0140] In some embodiments, the ingredients of the foam are melt blended by a method as described by Guerin et al. in U.S. Pat. No. 4,152,189. First, all solvent, if any, is removed from the ingredients by heating to a suitably elevated temperature of about 100° C. to about 200° C. or about 150° C. to about 175° C. at a pressure of about 5 Torr (667 Pa) to about 10 Torr (1333 Pa). Next, the ingredients are weighed into a container in the desired proportions, and the foam is formed by heating the contents of the container to a molten state while stirring.

[0141] In other embodiments, solvent blending is used to process the components of the foam. First, the components of the desired foam are dissolved in a suitable solvent and the mixture is then mixed or blended. Next, the solvent is removed to provide the foam.

[0142] In other embodiments, a physical blending device that can provide a combination of dispersive mixing, distributive mixing or dispersive mixing and distributive mixing can be used to prepare a uniform blend. Intermittent methods and continuous methods of physical blending can be used. In some embodiments, ethylene polymers and / or polar ethylene polar substances, peroxides, BiTEMPS and optional additives (activators such as metal oxides of antioxidants, pigments, tackifiers, fillers, nucleators, rubbers, stabilizers, processing aids, foaming agents) and foaming agents can be melt blended by Banbury mixers, intensive mixers, double-roll mills and extruders and their combinations. Adjustable time, temperature and shear rate to ensure that dispersion will not be prematurely crosslinked or foamed. After mixing the crosslinkable polymer composition, the crosslinkable polymer composition is formed into a desired shape. Thin plate rollers or calendering rollers can be used to prepare thin slices of appropriate size for foaming. Extruders can be used to shape the crosslinkable polymer composition into pellets.

[0143] Foaming is achieved by compression molding, injection molding, and extrusion and molding mixing of crosslinkable compositions. Foaming can be carried out by placing the crosslinkable composition into a compression mold (or autoclave) under a pressure, temperature, and time sufficient to complete the decomposition of peroxide and / or foaming agent. Before entering the compression mold / autoclave, or once the crosslinkable polymer composition is placed into the compression mold / autoclave, the crosslinkable polymer composition is impregnated with a foaming agent (physical foaming agent and / or chemical foaming agent). Pressure and heat are applied to the compression mold / autoclave. Rapid decompression and release of the compression mold / autoclave trigger foam formation. The resulting foam can be further shaped by thermoforming and / or compression molding as required.

[0144] When a free radical initiator is used, crosslinking of the foam article can be induced by activating the free radical initiator in the crosslinkable composition. The free radical initiator can be activated by exposing it to a temperature above its decomposition temperature. Alternatively, the free radical initiator can be activated by exposing it to radiation that causes the generation of free radicals from the free radical initiator. Similarly, the foaming or expansion of the foam article disclosed herein can be induced by activating the blowing agent in the crosslinkable composition. In some embodiments, the blowing agent can be activated by exposing it to a temperature above its activation temperature. Generally, the activation of crosslinking and foaming can occur simultaneously or sequentially. In some embodiments, the activation occurs simultaneously. In other embodiments, the activation of crosslinking occurs first, followed by the activation of foaming. In further embodiments, the activation of foaming occurs first, followed by the activation of crosslinking.

[0145] The crosslinkable polymer composition can be prepared or processed at a temperature below 150°C to prevent the decomposition of the blowing agent and the free radical initiator. When radiation crosslinking is used, the crosslinkable polymer composition can be prepared or processed at a temperature below 160°C to prevent the decomposition of the blowing agent. In some embodiments, the crosslinkable polymer composition can be extruded or processed through a die of a desired shape to form a crosslinkable structure. Then, the crosslinkable structure can be expanded and crosslinked at an elevated temperature (e.g., about 150°C to about 250°C) to activate the blowing agent and the free radical initiator, thereby forming a foam structure. In some embodiments, the foamable structure can be irradiated to crosslink the polymer material, which can then be expanded at a high temperature as described above.

[0146] Foam products disclosed herein can be prepared by conventional extrusion foaming methods. Foam products can be prepared as follows usually: heating ethylene polymers and / or polar ethylene polymers or polymer blends to form plasticized or molten polymeric materials, mixing a foaming agent therein to form a crosslinkable composition, and the crosslinkable composition is extruded through a die to form a foam product. Before mixing with a foaming agent, ethylene polymers and / or polar ethylene polymers can be heated to a temperature equal to or higher than its glass transition temperature or melting point. For example, a foaming agent can be mixed or blended into molten ethylene polymers and / or polar ethylene polymers with an extruder, a mixer, a blender, etc. A foaming agent can be mixed with molten ethylene polymers and / or polar ethylene polymers under elevated pressure, and the elevated pressure is enough to prevent the significant expansion of molten ethylene polymers and / or polar ethylene polymers and the foaming agent is uniformly dispersed therein usually. Optionally, before plasticizing or melting, the nucleating agent can be blended into the interpolymer melt, or dry mixed with the ethylene polymer and / or polar ethylene polymer. The crosslinkable polymer composition can be cooled to a relatively low temperature to optimize the physical properties of the foam structure. The crosslinkable polymer composition can then be extruded through a die of a desired shape or transported to a reduced pressure or lower pressure region to form a foam structure. The pressure in the lower pressure region can be lower than the pressure maintained by the crosslinkable polymer composition before extrusion through the die. The lower pressure can be higher than atmospheric pressure or lower than atmospheric pressure (vacuum), but is preferably at atmospheric pressure levels.

[0147] Foam or crosslinkable compositions disclosed herein may have a density of 150 kg / m to about 600 kg / m, 150 kg / m to about 500 kg / m, 150 kg / m to about 400 kg / m, 150 kg / m to about 350 kg / m, about 150 kg / m to about 300 kg / m, or about 150 kg / m to about 250 kg / m. In some embodiments, the density of foam disclosed herein is 150 kg / m to 500 kg / m. In other embodiments, the density of foam disclosed herein is 175 kg / m to about 500 kg / m. In other embodiments, the density of foam disclosed herein is 200 kg / m to about 500 kg / m.

[0148] The foaming method forms a foam product. The foam product is composed of a crosslinked foam composition. The crosslinked foam composition comprises an ethylene polymer and / or a polar ethylene polymer, BiTEMPS, and optional additives. In some embodiments, according to ASTM D3576, the foam product disclosed herein may have an average cell size of 0.05 g / cc to 5.0 g / cc, 0.2 g / cc to 2.0 g / cc, 0.1 g / cc to 1.5 g / cc, 0.1 g / cc to 1.0 g / cc, or 0.2 g / cc to 0.6 g / cc. In some embodiments, the crosslinked foam composition has uniform closed cells and a density of less than 0.2 g / cc, or 0.05 g / cc to 0.2 g / cc, or 0.05 g / cc to 0.15 g / cc.

[0149] In one embodiment, the foam article is a crosslinked foam composition consisting of an ethylene polymer, a bond of Structure 2 (formed by BiTEMPS), and optional additives. The ethylene polymer is an ethylene / octene multi-block copolymer. The crosslinked foam composition has uniform closed cells. The crosslinked foam composition comprises, consists essentially of, or consists of:

[0150] (i) 50 wt% to 99 wt% of an ethylene / octene multi-block copolymer having

[0151] (a) a density of 0.850 g / cc to 0.905 g / cc; and

[0152] (b) MI of 0.2 g / 10 min to 100 g / 10 min,

[0153] (ii) bonds of structure 2 (formed from 1 wt % to 15 wt % BiTEMPS methacrylate);

[0154] (iii) 0 wt%, or 0.1 wt% to 1.0 wt% of additives, the aggregate of ethylene polymer and bonds of Structure 2 (formed from BiTEMPS methacrylate) (and optional additives) totaling 100 wt% of the crosslinked foam composition, and the crosslinked foam composition has one, some or all of the following properties:

[0155] (iv) a density of 0.05 g / cc to 0.3 g / cc; and / or 0.08 g / cc to 0.25 g / cc; and / or

[0156] 0.1g / cc to 0.2g / cc

[0157] (v) a tensile strength of 0.7 MPa to 4 MPa; and / or 1 MPa to 3 MPa; and / or 1.5 MPa to 2.8 MPa

[0158] (vi) 40% to 90%; and / or 50% to 80%; and / or 55% to 75% rebound

[0159] (vii) Hardness of 5 to 60 (Asker C).

[0160] In one embodiment, the foam article is a crosslinked foam composition composed of a polar vinyl polymer, a structure 2 bond (formed by BiTEMPS) and optional additives. The crosslinked foam composition has uniform closed cells and a density of less than 0.2 g / cc, or from 0.05 g / cc to 0.2 g / cc, or from 0.05 g / cc to 0.15 g / cc.

[0161] In one embodiment, the foam article is a crosslinked foam composition consisting of a polar ethylene polymer, a bond of Structure 2 (formed by BiTEMPS), and optional additives. The polar ethylene polymer is ethylene vinyl acetate. The crosslinked foam composition has uniform closed cells. The crosslinked foam composition comprises, consists essentially of, or consists of:

[0162] (i) 5 to 100 wt. % of ethylene vinyl acetate having

[0163] (a) a density of 0.921 g / cc to 0.965 g / cc,

[0164] (b) MI of 0.3 g / 10 min to 500 g / 10 min,

[0165] (c) a vinyl acetate content of 1% to 40% by weight (based on the total weight of ethylene vinyl acetate);

[0166] (ii) bonds of structure 2 (formed from 1 wt % to 15 wt % BiTEMPS methacrylate);

[0167] (iii) 0 wt%, or 0.1 wt% to 1.0 wt% of additives, the aggregate of ethylenic polymer and bonds of Structure 2 (formed from BiTEMPS methacrylate) (and optional additives) totaling 100 wt% of the crosslinked foam composition.

[0168] The foams disclosed herein can take any physical form, such as spheres, cylinders, disks, cubes, prisms, sheets, slabs, foam slabs, or irregular shapes. In addition, they can be injection molded products, compression molded products, or extruded products. Other useful forms are expandable or cross-linkable particles, moldable foam particles or beads, and products formed by expansion and / or coalescence and welding of these particles. Non-limiting examples of suitable foam products include footwear (e.g., midsoles for footwear), packaging, sporting goods, building materials, and insulation.

[0169] In some footwear applications such as insoles, midsoles, outsoles, monosoles and insoles, the foams disclosed herein can be substantially cross-linked. According to ASTM D-2765-84 Method A, when the foam contains more than 5% gel, the foam is substantially cross-linked. In some embodiments, according to ASTM D-2765-84 Method A, the foam disclosed herein contains more than about 5% gel, more than about 10% gel, more than about 15% gel, more than about 20% gel, more than about 25% gel, more than about 30% gel, more than about 35% gel, or more than about 40% gel. In other embodiments, the foam disclosed herein contains less than about 95% gel. In another embodiment, the foam disclosed herein contains less than about 85% gel. In another embodiment, the foam disclosed herein contains less than about 75% gel.

[0170] I. Reprocessability

[0171] BiTEMPS methacrylate is a "dynamic crosslinker". The dynamic crosslinker BiTEMPS methacrylate enables the formation of a crosslinked network with ethylene polymers through disulfide bonds between the chains of the ethylene polymers (in the presence of a free radical initiator), thereby forming a crosslinked ethylene polymer composition. The crosslinking is dynamic because the disulfide bonds can be broken when the crosslinked ethylene polymer composition is subjected to a "reprocessing temperature", thereby allowing the chains to move and exchange, which is a temperature of 130°C to 300°C, or 140°C to 280°C, or 150°C to 270°C, or 160°C to 255°C. At the reprocessing temperature, the disulfide bonds in the crosslinked ethylene polymer composition are broken to form a reprocessable ethylene polymer composition. The reprocessable ethylene composition is cooled to below the reprocessing temperature to form a re-crosslinked ethylene polymer composition.

[0172] The dynamic crosslinker BiTEMPS methacrylate enables cyclic "reprocessing" to make new polymer articles. When the crosslinked ethylene polymer composition is heated to the reprocessing temperature, the disulfide bonds are broken or otherwise cleaved, allowing the previously crosslinked ethylene polymer composition to flow at the reprocessing temperature, thereby forming a "reprocessable ethylene polymer composition". Heating to the reprocessing temperature enables chain scission and polymer chain flow, thereby allowing the ethylene composition to be easily reshaped. At the reprocessing temperature, the reprocessable ethylene polymer composition is no longer crosslinked, but is flowable, allowing the now flowable, reprocessable ethylene composition (with BiTEMPS methacrylate) to be shaped and / or manufactured into a new preform or article. When cooled to below the "reprocessing temperature", the disulfide bonds are formed again, the network is reestablished, and the re-crosslinked ethylene composition is formed in a new article configuration, returning to high viscosity (no flow at room temperature) and resistance to mechanical deformation indicating a crosslinked network. When the newly formed article of the reprocessable ethylene polymer composition is cooled to below the reprocessing temperature, the disulfide bonds in the reprocessable ethylene polymer composition are reestablished and the ethylene polymer (with BiTEMPS methacrylate) becomes a recrosslinked ethylene polymer composition in the shape of the newly manufactured article. Below the reprocessing temperature, the network disulfide bonds are stable and the recrosslinked ethylene polymer composition exhibits high viscosity and resistance to mechanical deformation indicative of the crosslinked network. This cycle of crosslinking / reprocessing / recrosslinking and manufacturing into new articles can be repeated.

[0173] Without being bound by a particular theory, the number of "reprocessing" cycles possible for the crosslinked ethylene compositions of the present invention (before competing thermal and oxidative permanent crosslinking occurs and prevents further reprocessing) can be determined by calculating the ratio of the melt viscosities of the crosslinked ethylene polymer composition before and after the reprocessing cycle. For the reprocessable, crosslinked ethylene polymer composition, the ratio of the Mooney viscosity after reprocessing to the Mooney viscosity before reprocessing is from 0.5 to 5, or from 0.7 to 3, or from 0.9 to 2, or from 0.95 to 1.2.

[0174] Other metrics used to monitor the number of "reprocessing" cycles possible for the BiTEMPS methacrylate dynamic crosslinker before competing oxidative permanent crosslinking occurs include visual observation. The mechanically deformed formed film is heated to the reprocessing temperature and visually inspected to determine if the mechanically deformed film has healed to form a stable film.

[0175] The present disclosure provides a method. In one embodiment, the method includes: heating a foam article to a reprocessing temperature. The foam article is composed of a cross-linked foam composition, which is composed of the following: (i) an ethylene polymer and / or a polar ethylene polymer, (ii) a bond of Structure 2 (formed by 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate)), and (iii) an optional additive. The method includes forming the foam article into a reprocessable polymer composition (a reprocessable ethylene polymer or a reprocessable polar ethylene polymer) at a reprocessing temperature. The method includes forming the reprocessable polymer composition (a reprocessable ethylene polymer composition or a reprocessable polar ethylene polymer composition) into a reprocessable preform at a reprocessing temperature. The method includes cooling the reprocessed preform to below the reprocessing temperature and forming a second article composed of a recrosslinked polymer composition, wherein the recrosslinked polymer composition is composed of: (i) a vinyl polymer and / or a polar vinyl polymer and (ii) a bond of Structure 2 (formed by BiTEMPS methacrylate).

[0176] The second article may be the same as or different from the first article.

[0177] In one embodiment, the forming step is a procedure selected from the group consisting of injection molding, extrusion molding, thermoforming, blow molding, overmolding, insert molding, blow molding, casting, tentering, compression molding, and combinations thereof.

[0178] Non-limiting examples of suitable articles (second articles) for the re-crosslinked (polar) ethylene polymer (with BiTEMPS methacrylate) compositions of the present invention include foam articles, elastic films; elastic fibers; soft-touch items such as toothbrush handles and appliance handles; pads and profiles; three-dimensional loop materials; coatings for conductors; adhesives (including hot melt adhesives and pressure sensitive adhesives); footwear (including soles and shoe insoles); automotive interior parts and profiles; foam articles (both open-cell and closed-cell foams); impact modifiers for other thermoplastic polymers such as high-density polyethylene, isotactic polypropylene or other olefin polymers; coated fabrics; hoses; pipes; weather strips; lid linings; flooring; and combinations thereof.

[0179] Another embodiment provides a method for reprocessing a foam article. In one embodiment, the reprocessing includes converting the foam into small pieces, mixing optional additives into the small pieces, heating the mixed product to a reprocessing temperature, or a combination of the above methods. The conversion method includes pressing, calendaring, cutting, shearing, or a combination of the above methods at low temperature, room temperature, or high temperature. The foam composition is composed of: (i) an ethylene polymer and / or a polar ethylene polymer, (ii) a bond of structure 2 (formed by 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate)), and (iii) optional additives. The method includes cooling the reprocessed preform to below the reprocessing temperature and forming a second article composed of a recrosslinked polymer composition, which is composed of: (i) an ethylene polymer and / or a polar ethylene polymer and (ii) a bond of structure 2 (formed by BiTEMPS methacrylate).

[0180] By way of example and not limitation, some embodiments of the present disclosure will now be described in detail in the following examples.

[0181] 1. Materials

[0182] The materials used in the comparative samples (CS) and the inventive examples (IE) are provided in Table 1 below.

[0183] Table 1 - Materials

[0184]

[0185] 2. Synthesis of BiTEMPS Methacrylate

[0186] To synthesize BiTEMPS methacrylate, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (8.78 g, 39.0 mmol, provided by TCI America) was first dissolved in anhydrous petroleum ether (about 90 mL, provided by Sigma-Aldrich, dried over molecular sieves for 48 hours before use) and cooled to -70 °C in a dry ice / acetone bath. Afterwards, sulfur monochloride (1.30 g, 9.7 mmol, provided by Sigma-Aldrich) was dissolved in anhydrous petroleum ether (about 1.25 mL) and added dropwise to the reaction vessel over a 30-minute period. The solution was stirred at -70 °C for another 30 minutes and at room temperature for 15 minutes. Next, BiTEMPS methacrylate was precipitated by pouring the reaction solution into a large amount of distilled water and stirring at room temperature overnight. The precipitate was collected, vacuum filtered, and vacuum dried at 60 °C for 48 hours to obtain BiTEMPS methacrylate as shown in the following structure 1.

[0187]

[0188] 3. Formulation - Crosslinkable Composition

[0189] A. Embodiments of the Invention

[0190] INFUSE 9000 (or EVA 265), dicumyl peroxide, and BiTEMPS methacrylate were combined (in the amounts shown in Table 2 below) and batch mixed at 100° C. The properties are provided in Table 2 below.

[0191] B. Comparison samples

[0192] 400 g of INFUSE pellets and 4 g of DCP powder were loaded into a PTFE bottle. The bottle was sealed and placed on a roller with a rolling speed of 65 RPM. The roller was then transferred to a 55° C. hot air oven for 2 hours. After reaching the required time, the roller was stopped and the bottle was transferred out of the oven and cooled at room temperature.

[0193] After mixing, each formulation was transferred to a 172mm×172mm×7mm mold. The mold was further placed in a hot press. The hot press was preheated at 125°C for 3 minutes, followed by degassing 8 times, and then the mold was transferred to a second hot press at 180°C. In the second hot press, the mold was pressed at 180°C and 280 kilonewtons (kN) pressure, cured for 10 minutes, and then cooled to 45°C. The pressure was then removed to form a cross-linked composition. Each cross-linked composition was fed into an autoclave equipped with a heating unit and a gas injection valve. The autoclave was heated to the desired temperature (120°C-150°C). At the same time, a blowing agent was injected into the autoclave for saturation (0.5 hours to 2 hours). The autoclave pressure varied depending on the polymer type. The autoclave pressure ranged from 50 bar to 200 bar. After the cross-linked composition was saturated with the blowing agent, rapid decompression occurred and a foam block was prepared. The foam block was conditioned at room temperature for 24 hours. The corresponding properties are summarized in Table 2.

[0194] Table 2 - Recipe

[0195]

[0196] *IE-A / IE-B were each pre-molded at 80°C for 10 minutes to fill the shape of a square mold (1.517 in x 1.517 in x 0.246 in); the composition was then held at 180°C for 20 minutes under 40,000 lbs force, the mold pressure was released and the foam was allowed to pop out of the mold.

[0197] 4. Reprocessability

[0198] A. The crosslinked compositions selected in Table 2 were tested for reprocessability. The crosslinked compositions were cut into small pieces manually using scissors. The small pieces were transferred to a mold with dimensions of 120 mm x 75 mm x 3 mm and reprocessed at 280 KN pressure for 10 minutes at different temperatures. The results are reported in Table 3 below.

[0199] Table 3 - Reprocessability

[0200]

[0201] Figure 1 Photographs of non-reprocessable comparative samples: CS-3Reprocess180, CS-3Reprocess250 and IE-3Reprocess130 are shown. Figure 1 Photographs of reprocessable examples IE-3Reprocess180 and IE-3Reprocess250 are shown.

[0202] B. Figure 3A and Figure 3B : are photographs showing the corresponding IE-A-foam and IE-B-foam, respectively. The IE-A-foam and IE-B-foam were each cut into small pieces by hand using scissors. The small pieces were transferred to a mold and compression molded at 180°C, 40,000 psi for 2 minutes. Figure 4A and Figure 4B The corresponding IE-A-foam and IE-B-foam are shown, each as a reprocessed homogeneous compression molded disk, thereby demonstrating that the IE-A-foam and IE-B-foam, respectively, are fully reprocessable.

[0203] 5. Preparation of Recycled Foam

[0204] The reprocessed compositions (from Table 3) were foamed under the same conditions as described in paragraph

[0096] . The properties of the foams are provided in Table 4 below.

[0205] Table 4 - Foam

[0206] Starting composition CS-3 IE-3 IE-3 IE-3 Foam Name CS-3 Foam IE-3 Foam IE-3reprocess180 foam IE-3reprocess250 foam Density(g / cc) 0.1544 0.1248 0.1149 0.0581 Rebound(%) 74 72 77 70 Tensile strength (MPa) 2.16 2.56 2.62 1.03 Hardness (Asker C) 54 45 55 16 Compression set (%) 16.4 26.7 22.0 85.9

[0207] *IE-A foam compression molded at 180°C, 40,000 psi for 2 minutes

[0208] Figure 2 Photos of foams: CS-3 foam, IE-3 foam, IE-3reprocess180 foam, and IE-3reprocess250 foam are shown.

[0209] It is particularly intended that the present disclosure is not limited to the embodiments and descriptions contained herein, but includes modifications of those embodiments including parts of the embodiments and combinations of elements of different embodiments as appear within the scope of the following claims.

Claims

1. A foam product, comprising: A cross-linked foam composition formed from a starting material comprising a polymer selected from the group consisting of ethylene polymers, polar ethylene polymers, and combinations thereof; and 2,2,6,6-Tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate).

2. The foam article of claim 1, wherein the crosslinked foam composition comprises: The polymer selected from the group consisting of ethylene polymers, polar ethylene polymers, and combinations thereof; and A bond with structure (2) 3. The foam article according to any one of claims 1 to 2, wherein the polymer is an ethylene-based polymer.

4. The foam article of claim 3, wherein the ethylene-based polymer is an ethylene / α-olefin multi-block copolymer.

5. The foam article of claim 4, wherein the cross-linked composition is formed from a starting material comprising: 50 wt% to 99 wt% of said ethylene / α-olefin multi-block copolymer; and 1 wt % to 15 wt % of said BiTEMPS (methacrylate).

6. The foam article of claim 2, wherein the polymer is a polar vinyl polymer.

7. The foam article of claim 6 wherein the polar vinyl polymer is ethylene vinyl acetate.

8. The foam article of claim 7, wherein the cross-linked composition is formed from a starting material comprising: 50 to 99 weight percent of said ethylene vinyl acetate; and 1 wt % to 15 wt % of said BiTEMPS (methacrylate).

9. The foam article according to any one of claims 1 to 8, wherein the foam article has a property selected from the group consisting of: Density from 0.05g / cc to 0.3g / cc, 0.7MPa to 4MPa tensile strength, 40% to 90% rebound, 5 to 60 hardness (Asker C), and A combination of them.

10. A foam product, comprising: A cross-linked composition, comprising: a polymer selected from the group consisting of ethylene polymers, polar ethylene polymers, and combinations thereof; and A bond with structure (2) 11. A method comprising: The foam article is heated to a reprocessing temperature, the foam article being comprised of a cross-linked composition comprising: (i) a polymer selected from the group consisting of ethylene polymers, polar ethylene polymers, and combinations thereof; and (ii) A bond having structure (2) forming the foam article into a reprocessable polymer composition at the reprocessing temperature; forming the reprocessable polymer composition into a reprocessable preform at the reprocessing temperature; cooling the reprocessed preform to below the reprocessing temperature; as well as A second article is formed consisting of a re-crosslinked polymer composition consisting of: (i) a polymer selected from the group consisting of the ethylene polymer, the polar ethylene polymer, and a combination thereof; and (ii) A bond having the structure (2).

12. The method of claim 11, wherein the polymer is an ethylene-based polymer.

13. The method of claim 11, wherein the polymer is a polar vinyl polymer.

Citation Information

Patent Citations

  • Method of utilizing polyacrylic hot-melt adhesives

    US4152189A